The Effect Of Using Authentic Material As Media On The Students’ Achievement In Listening - Evri Yenny Siregar; Imelda Damayanti Manurung (English Teaching and Linguistics Journal (ETLiJ), 2020)
The objective of this research is to investigate whether the use of Authentic material as media has a significant effect to the students’ achievement in listening. The population of this research was the eleven grade students of SMK Swasta Nurhasanah 2 Medan year 2012/2013. The total number of population was 50 students in two classes: class XI.AK.1 was 25 students and class XI.AK.2 was 25 students, all the population were takes. So, there were 50 students as a sample. The sample was divided into two groups. The first group consist of 25 students was taught by authentic material using news items as media and the second group consist of 25 students was taught by non authentic material using text book as media. This research used quantitative method and experimental research. The instrument in collecting data was essay test of complete the missing words. The ability of students before giving authentic material as media is 56% or 14 students who were categorized as able and 44% or 11 students who were categorized as unable. The ability of students after giving authentic material as media is 100% or 25 students who were categorized as able.The finding indicates that t-test (3,72) was higher than t- table (2,01) with the level of significant 0,05 and the degree of freedom (df) = 48. The findings showed that the hyporesearch alternative (Ha) is accepted. It means that using authentic material as media significantly effect to improve the students’ achievement in Listening.